An empirical investigation of the relationship between regional economic growth and structural change - John Hugh Llewellyn Dewhurst (European Regional Science Association (ERSA), 2002)
It is well recognized that changes in the economic performance of regions would normally be associated with a degree of structural change. In any region it is extremely improbably that all industrial sectors are growing or declining at the same rate. This paper seeks to examine the nature of the interrelationship between economic growth and the extent of structural change that takes place in a region. Using a simple model it is shown that, if all industries are growing, regions that have a relative concentration in faster growing industries will not only grow faster but also experience a more rapid degree of structural change. If, as is more realistic, some industries are declining then the relationship between the rate of growth in a regional economy and the speed of structural change is more complex, for the contraction of industries also implies a measure of structural adjustment. In addition it may be noted that structural change imposes adjustment costs on the economy so that large-scale structural change may impede growth. After considering how best to measure the rate of structural change, the paper uses UK regional data to examine the relationship between that rate and the rate of growth on the regional economies. Attention is focused on establishing the nature of the causal relationship between the two variables, the non-symmetric nature of the relationship and the degree to which significant structural change impedes economic growth.
Keywords: 330